Reports of Judgments, Advisory Opinions and Orders - Intl. Tribunal for the Law of the Sea, Intl. Tribunal for the Law of the (Reports of Judgments, Advisory Opinions and Orders / Recueil des Arrêts, Avis Consultatifs et Ordonnances Ser., 2017)
This volume contains the decisions rendered by the Tribunal in the year 2016 in English and French: The Judgment delivered on 4 November 2016 in the preliminary objections phase of The M/V "Norstar" Case (Panama volume Italy ) as well as procedural orders issued in M/V "Norstar" and the Dispute concerning delimitation of the maritime boundary between Ghana and Côte d'Ivoire in the Atlantic Ocean (Ghana/Côte d'Ivoire) . Le présent volume contient en français et en anglais les décisions rendues par le Tribunal au cours de l'année 2016 : l'arrêt du 4 novembre 2016 sur les exceptions préliminaires dans l'Affaire du navire « Norstar » (Panama c. Italie) ainsi que des ordonnances procédurales rendues dans Navire « Norstar » et le Différend relatif à la délimitation de la frontière maritime entre le Ghana et la Côte d'Ivoire dans l'océan Atlantique (Ghana/Côte d'Ivoire) .